Kajian User Centric Government: Analisis Performa Aplikasi Mobile JKN di BPJS Kesehatan Karawang - Azmi Ayu Fadhilah Burhanudin; Lina Aryani; Dewi Noor Azijah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to explore the experiences of individuals when using the JKN mobile application. This research focuses on how the performance of the JKN mobile application can unravel the problems that exist in the health care sector and can help users to get proper, efficient, and effective health services. This research method uses phenomenological qualitative research through observation, interviews and other documents that support the research. BPJS Kesehatan as a service provider needs to supervise the JKN mobile application. BPJS Kesehatan has the authority to regulate and be responsible for the performance of the JKN mobile application. Performance of the JKN mobile application still has some problems such as errors in some time and failing to load data in the doctor's schedule feature.